Enhancing English Language Learners’ Listening Comprehension through Listening Strategies Instruction - Sitti Hadijah; Shalawati Shalawati (UIR Press, 2018)
This paper is a part of research project carried out to enhance the English learners’ listening comprehension through listening strategies instruction. The research worked on classroom action research design, conducted in two cycles by involving a group from fresh year English learners in English study program of Teacher Training and Education Faculty, Universitas Islam Riau on 2017/2018 academic year. The findings revealed gradual improvement of the students’ performances in doing the listening tests. At the first cycle, the students could reach 25 out of 40 questions, in which this number is four points less than the students’ achievement in cycle 2. Then, in range 10-25 questions of correct answers in cycle 1 could be reached by 24 students, while in cycle 2, there were 32 students got correct answers at that range. Furthermore, there were 6 students could reach less than 10 questions correctly, beside that there were only 3 students in cycle 2. In conclusion, there have been improvement of the students’ achievements in listening tasks provided in all meetings during cycle 1 and 2. Although they found challenges in completing the tests, the teachers’ assistances in guiding them to apply some strategies contributed towards the improvement of their performances in listening. Keywords: enhancing, listening comprehension, listening strategies instruction